Correspondence from Honey Toda to Betty Salzman, December 25, 1942 - Honey Toda::::::author:::
Personal letter describes Christmas Day in the internment camp, mentioning the wind, dust, and cold conditions along with the beauty of the Sierras and her first view of snow. Toda also describes a Christmas party that drew people of all ages, and asks about Salzman's work and if Salzman is affected by gas rationing or other shortages, noting that they have felt effects of rationing at Manzanar.